Production of added value bacterial lipids through valorisation of hydrocarbon-contaminated cork waste - Castro, Rita (2017)
This work demonstrates that cork used as oil-spill sorbents, contaminated with liquid hydrocarbons, herein demonstrated with hexadecane, can be biologically treated by Rhodococcus opacus B4 with concomitant lipids production. R. opacus B4 consumed up to 96% of hexadecane (C16) impregnated in natural and regranulated cork sorbents after 48 h incubation, producing 0.59 ± 0.06 g of triacylglycerol (TAG) g 1 of C16 consumed with a TAG content of 0.60 ± 0.06 g g 1 of cellular dry weight (CDW) and 0.54 ± 0.05 g TAG g 1 of C16 consumed with a TAG content of 0.77 ± 0.04 g g 1 (CDW), respectively. TAG was mainly composed by fatty acids of 16 and 18 carbon chains demonstrating the feasibility of using it as raw material for biodiesel production. In addition, the obtained lipid-rich biomass (whole cells) can be used for biomethane production, at a yield of 0.4 L CH4 g 1 (CDW). The obtained results support a novel approach for management of oil-spill contaminated cork sorbents through its valorisation by producing bacterial lipids, which can be used as feedstocks for biofuels production.